Versatile Coordination of AgI and CuI Ions towards cyclo‐As5 Ligands. Issue 38 (1st June 2021) - Moussa, Mehdi Elsayed; Fleischmann, Martin; Balázs, Gábor; Virovets, Alexander V.; Peresypkina, Eugenia; Shelyganov, Pavel A.; Seidl, Michael; Reichl, Stephan; Scheer, Manfred
Abstract: The reactions of the cyclo ‐As5 complex [Cp*Fe(η 5 ‐As5 )] (B ) with the Ag I and Cu I salts of the weakly coordinating anion (WCA) [FAlOC6 F10 (C6 F5 )3 ] − ([FAl] − ) are studied. These reactions allow the synthesis of the mononuclear complexes [M(η 5 : η 2 ‐B )2 ][FAl] (M=Ag (1 ), Cu (2 )) when a ratio of B /M(FAl) 2 : 1 is used. Compound 1 shows an unusual disorder of the central Ag I cation between two π‐coordinating cyclo ‐As5 ligands, which is absent in 2 pointing to a weak interaction of the Ag center towards the cyclo‐As5 ligands in B . When the ratio of B /Ag(FAl) is changed to 3 : 1 or 1 : 1, the respective coordination compounds [Ag(η 2 ‐B )3 ][FAl] (3 ) and [Ag2 (η 2 : η 2 ‐B )2 ][FAl]2 (4 ) are accessible. The coordination modes of the cyclo ‐As5 units in 1, 3 and 4 are all different, reflecting the adaptive coordination behavior of B towards Ag I ions. The optimized geometries in the gas phase of 1 –4 are determined by DFT calculations to support the bonding situation observed in their solid‐state structures. Abstract : The first homoleptic Ag I and Cu I coordination compounds of the cyclo ‐As5 complex [(Cp*Fe(η 5 ‐As5 )] (B ) are obtained from its reaction with the M[FAlOC6 F10 (C6 F5 )3 ] (M(FAl); M=Ag, Cu) salts. Varying the ratio of the starting materials is reflected in a diversity of the isolated supramolecular assemblies (1, 3, 4 ) as products. The coordination mode of the cyclo ‐As5 units in each of 1, 3 and 4 is different revealing the pronounced adaptive coordination of B towards Ag I ions.